Post-harvest Rots of Tomato Fruits - Fakorede, Adekunle (Obafemi Awolowo University, 2014)
In a study of post-harvest fruit rot disease of tomatoes in South western Nigeria, the soft watery rot was the most prevalent accounting for more than 60% of total fruit rots during the rainy season. Aspergillus niger, Geotrichum candidum, Mucor hiemalis and Pichia kluyveri were organisms established as incitants of the rot. A. niger and G. candidum were major virulent pathogens while M. hiemalis and P. kluyveri were mild ratters.